A panel of four decreased serum microRNAs as a novel biomarker for early Parkinson's disease. (17th February 2016) - Dong, Hui; Wang, Cheng; Lu, Sunbin; Yu, Cuiyu; Huang, Lei; Feng, Wuruo; Xu, Hui; Chen, Xi; Zen, Ke; Yan, Qiao; Liu, Weiguo; Zhang, Chunni; et al.
Abstract: Context: Sensitive, non-invasive biomarkers that facilitate Parkinson's disease (PD) detection and stage assignment are currently unavailable. Objective: The objective of this study is to investigate the potential of circulating microRNAs (miRNAs) as novel biomarkers for PD. Materials and methods: Solexa sequencing technology and quantitative real-time PCR were applied to screen and verify altered serum miRNAs in PD patients. Results: Serum miR-141, miR-214, miR-146b-5p, and miR-193a-3p were decreased significantly in PD patients compared with controls. Furthermore, the 4-miRNA panel enabled the differentiation of HY stage 1 and 2 PD patients from controls. Discussion and conclusion: The four serum miRNAs may represent novel biomarkers for the early detection of PD.